Single Photon Emission Computed Tomography-Computed Tomography (SPECT-CT) Use in Osteosarcoma with Lung Uptake - Abdul Hamid, Khadijah; Ahmad Sarji, Sazilah (Scientific Research Publishing, 2014)
A 15-year-old patient with osteosarcoma of left distal femur underwent a bone scan with Tc-99m hydroxymethylenediphosphonate (HDP). Whole body bone scan revealed extensive bone and thoracic metastases. Single Photon Emission Computed Tomography-Computed Tomography (SPECT-CT) of the thorax localized the uptake at pleura and lung nodules. In this case study we want to share our experience using SPECT-CT.